Strategic analytics : integrating management science and strategy - Kunc, Martin (Hoboken, NJ : John Wiley & Sons, 2018)
Defines common ground at the interface of strategy and management science and unites the topics with an original approach vital for strategy students, researchers and managers Strategic Analytics: Integrating Management Science and Strategy combines strategy content with strategy process through the lenses of management science, masterfully defining the common ground that unites both fields. Each chapter starts with the perspective of a certain strategy problem, such as competition, but continues with an explanation of the strategy process using management science tools such as simulation. Facilitating the process of strategic decision making through the lens of management science, the author integrates topics that are usually in conflict for MBAs: strategy and quantitative methods. Strategic Analytics features multiple international real-life case studies and examples, business issues for further research and theory review questions and exercises at the end of each chapter. Strategic Analytics starts by introducing readers to strategic management. It then goes on to cover: managerial capabilities for a complex world; politics, economy, society, technology, and environment; external environments known as exogenous factors (PESTE) and endogenous factors (industry); industry dynamics; industry evolution; competitive advantage; dynamic resource management; organisational design; performance measurement system; the life cycle of organisations from start-ups; maturity for maintaining profitability and growth; and finally, regeneration.' -Developed from the author's own Strategy Analytics course at Warwick Business School, personal experience as consultant, and in consultation with other leading scholars -Uses management science to facilitate the process of strategic decision making -Chapters structured with chapter objectives, summaries, short case studies, tables, student exercises, references and management science models -Accompanied by a supporting website Aimed at both academics and practitioners, Strategic Analytics is an ideal text for postgraduates and advanced undergraduate students of business and management.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Management science; Decision making; Strategic planning; Electronic books